2015
DOI: 10.1055/s-0035-1544974
|View full text |Cite|
|
Sign up to set email alerts
|

Modified Protocol Decreases Surgical Site Infections after Total Knee Arthroplasty

Abstract: We investigate the effectiveness of a comprehensive aseptic protocol in reducing surgical site infection (SSI) after knee arthroplasty in a single medical center with a high prevalence of MRSA. A database of all patients in a single center undergoing primary knee arthroplasty between 2005 and 2011 was reviewed for SSI using Centers for Disease Control criteria and AAOS guidelines. All patients were treated with an aseptic protocol consisting of the following: preoperative 2% mupirocin nasal ointment and 0.4% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…In the studies that demonstrated a positive effect, however, the infection rate was between 1.6 and 5.5%, and was thus higher than the incidence of less than 1% described for many centers with optimized perioperative prophylaxis [17][18][19][20][21] . It is unclear whether locally applied vancomycin can also lower the risk of infection in an optimized setting with an already low infection rate.…”
mentioning
confidence: 69%
“…In the studies that demonstrated a positive effect, however, the infection rate was between 1.6 and 5.5%, and was thus higher than the incidence of less than 1% described for many centers with optimized perioperative prophylaxis [17][18][19][20][21] . It is unclear whether locally applied vancomycin can also lower the risk of infection in an optimized setting with an already low infection rate.…”
mentioning
confidence: 69%
“…The secret to success probably consists of a well-balanced combination of preventative interventions that will result in a reduction in the number of PJIs in the population and the probability of PJI in a patient [212]. Whether finding it will require trial and error or be facilitated by more modern tools remains to be seen.…”
Section: Who Is the Best Provider?mentioning
confidence: 99%
“…4 This concept led to the use of weight-based drug dosing, instead of conventional fixed drug doses for both, cefazolin and vancomycin. 26,27 The recommended doses for weight-based dosing of cefazolin is 2-g intravenous for patients weighing less than 120 kg and 3-g intravenous for those patients weighing more than 120 kg. 27 Traditionally, a fixed dose (1 g) of vancomycin has been used for antibiotic prophylaxis.…”
Section: Dual Prophylactic Antibiotics: Dosage and Timing Of Administmentioning
confidence: 99%
“…26,27 The recommended doses for weight-based dosing of cefazolin is 2-g intravenous for patients weighing less than 120 kg and 3-g intravenous for those patients weighing more than 120 kg. 27 Traditionally, a fixed dose (1 g) of vancomycin has been used for antibiotic prophylaxis. However, recent evidence has shown that vancomycin levels drops below 15 mg/L in 60% of the patients who were given a 1-g dose, in contrast to, only 12% of the patients who were treated with a weight-based approach.…”
Section: Dual Prophylactic Antibiotics: Dosage and Timing Of Administmentioning
confidence: 99%